The Creativity of The Quran Hadith Teacher to Overcome Students' Learning Difficulties - Julhadi Julhadi; Akhmad Sirojuddin; Syamsul Arifin; Elihami Elihami; Rokhmatin Nazilah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Learning does not always go according to what is expected. The existence of problems during the learning process is a challenge. The subjects of the Qur'an Hadith have been found learning difficulties for students. So to understand the learning difficulties experienced by students and know and analyze the creative efforts of Qur’an teachers Hadith in overcoming learning difficulties, this research was conducted at madrasah International Standard in Mojokerto. The researchers use a qualitative approach, a type of case study using; collects data, analyses, and concludes field data. As for the research findings: 1) Difficulties faced by students include; difficulty reading, writing, memorization, and understanding material 2) While creativity carried out by the Master of the Qur'an Hadith to overcome learning difficulties, namely; a) On the difficulty of reading and writing; Personal approach, Cooperate with the Muadalah program; (a) Reading the Quran with tajwid (b) Providing writing and making up skills in Arabic, b) Difficulty memorizing material; Giving short verses, providing motivation, instructing repeat memorization giving time lag during learning c) Difficulty understanding the material; Giving repetition of the material,  using simple language,  providing motivation, interpreting verse every word.